Study of aflatoxin M1 level in the collected raw cow milk from milk collection centers in Tabriz - M.H Movassagh; S Adinehvand (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2013)
Aflatoxins are a group of mycotoxins mainly produced by common fungi Aspergillus flavus, A. parasiticus and A. nomius. Aflatoxin M1 (AFM1) is the major metabolite of aflatoxin B1. AFM1 is also known to be hepatotoxic and carcinogenic. The purpose of this study was to investigate the contamination level of AFM1 in raw cow milk of Tabriz. A total of 90 raw cow milk samples was collected randomly from Tabriz suburb milk-collection-centers between July to September 2012. Determination of AFM1 was based on ELISA assay. Based on the results, AFM1 was found in 100% of cow milk samples. The mean contamination rate was 148.37 ± 19.27 ng/l. Moreover, 37.77% of cow milk samples had the contamination level over the maximum tolerance limit (100 ng/l) accepted by Iranian National Standard. It was concluded that high incidence and contamination level of AFM1 in cow's milk is of great concern. The periodic monitoring of cow raw milk for the contamination of AFM1 in Tabriz area is recommended.